2020
DOI: 10.1088/1751-8121/abc5d2
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced desorption of uniform block copolymers

Abstract: We investigate self-avoiding walk models of linear block copolymers adsorbed at a surface and desorbed by the action of a force. We rigorously establish the dependence of the free energy on the adsorption and force parameters, and the form of the phase diagram for several cases, including AB-diblock copolymers and ABA-triblock copolymers, pulled from an end vertex and from the central vertex. Our interest in block copolymers is partly motivated by the occurrence of a novel mixed phase in a directed walk model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…by definition of H * a . If λ(y 1/g ) > κ(a), then ψ(a, y 1/g ) = λ(y 1/g ), and by lemma 4 in reference [22], for almost every y > (λ −1 (κ(a))) g , lim n→∞ (H * a /n) = y d dy λ(y 1/g ) = β > 0. On the other hand, if λ(y 1/g ) < κ(a), then the right hand side of equation ( 32) is independent of y, and so one may assume, without loss of generality, that for arbitrary small ǫ > 0 there exists an N ǫ such that H * n < ǫn for all n > N ǫ .…”
Section: A Lower Boundmentioning
confidence: 90%
See 1 more Smart Citation
“…by definition of H * a . If λ(y 1/g ) > κ(a), then ψ(a, y 1/g ) = λ(y 1/g ), and by lemma 4 in reference [22], for almost every y > (λ −1 (κ(a))) g , lim n→∞ (H * a /n) = y d dy λ(y 1/g ) = β > 0. On the other hand, if λ(y 1/g ) < κ(a), then the right hand side of equation ( 32) is independent of y, and so one may assume, without loss of generality, that for arbitrary small ǫ > 0 there exists an N ǫ such that H * n < ǫn for all n > N ǫ .…”
Section: A Lower Boundmentioning
confidence: 90%
“…The adsorption and desorption of block copolymers is interesting because of their application in steric stabilization of dispersions where one type of block tends to adsorb on the surface of the colloidal particle while the other type of block is in the surrounding medium [8,33] (in which the colloidal particle is dispersed). The properties of the adsorbed block copolymer were modelled using a self-avoiding walk model of linear diblock and triblock copolymers in reference [22]. The adsorbed copolymer is pulled from the surface with the force being applied at the end or at the centre of the polymer.…”
Section: Notation and A Brief Reviewmentioning
confidence: 99%
“…The adsorption and desorption of block copolymers is interesting because of their application in steric stabilization of dispersions where one type of block tends to adsorb on the surface of the colloidal particle while the other type of block is in the surrounding medium [7,33] (in which the colloidal particle is dispersed). The properties of the adsorbed block copolymer were modelled using a self-avoiding walk model of linear diblock and triblock copolymers in reference [22]. The adsorbed copolymer is pulled from the surface with the force being applied at the end or at the centre of the polymer.…”
Section: Notation and A Brief Reviewmentioning
confidence: 99%
“…The adsorbed copolymer is pulled from the surface with the force being applied at the end or at the centre of the polymer. In reference [22] it is shown that the phase diagrams of these models have numerous phases, including free, adsorbed, and ballistic phases while some phases have a mixed adsorbed-ballistic character. Some of the results of this paper will be used here.…”
Section: Notation and A Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation